Ultrasonographic Evaluation of Dogs with Cranial Cruciate Ligament Rupture Undergoing to Arthrotomy - Fasanelo Gomes, Luanna Ferreira; Bregadioli, Thales; Filippo Hagen, Stefano Carlo (Acta Scientiae Veterinariae, 2019)
Background: The cranial cruciate ligament rupture (CrCLR) is the most common disease of the stifle joint in dogs. One of the major concerns in the assessment of these animals is diagnosing the presence of a medial meniscus tears, which is a frequent consequence due to the instability of the joint. Ultrasonography is indicated in the evaluation of the menisci from human and canine patients, and the results are similar to magnetic resonance imaging. The aim of this study was to compare the ultrasonography and the arthrotomy in the evaluation of the cranial cruciate ligament and medial meniscus of dogs with CrCLR undergoing surgery for stifle stabilization. Materials, Methods & Results: Ultrasonographic examination was performed prior to arthrotomy in 23 dogs with diagnosis of complete CrCLR and five with suspected partial CrCLR undergoing for stifle joint stabilization surgery. The ultrasonography identified the complete rupture in 82.6% and the arthrotomy in 100% of the joints with this diagnosis. In the joints with suspected CrCLR during the clinical exam, arthrotomy and ultrasonography identified respectively three and four joints with partial CrCLR, and two and one with healthy ligaments. There was no difference between the two techniques in the assessment of the cranial cruciate ligament (P = 0.20). The ultrasonography identified medial meniscal tears in 39.3%, while arthrotomy was found in 21.4% (P = 0.0006) of the joints. The most frequent meniscal tear type observed in the arthrotomy was folded caudal horn. The ultrasonography was able only in differentiate presence and absence of meniscal injury. Besides the real tear that affects the meniscus morphology, the ultrasound also identified echogenicity and echotexture changes in the medial (5/28) and lateral (8/28) menisci. Other changes observed in all joints evaluated by ultrasound were the presence of effusion and synovial membrane thickening. Discussion: The complete and almost complete CrCLR are diagnosed by clinical examination through the evaluation of instability of the stifle joint, which is not possible in partial CrCLR in stable joints. In this study of the five evaluated stable joints, the ultrasound correctly identified the partial CrCLR in three joints and the ligament integrity in one of the joints when compared to arthrotomy. In animals with stifle joint instability the meniscus assessment is fundamental as it is one of the main causes of persistent lameness in dogs subjected to conservative or surgical treatment. Ultrasonography cannot differentiate the types of meniscal tears but identified approximately 1.8 times more medial meniscus tears compared to arthrotomy. Despite the bucket handle being the most common tear of medial meniscus in dogs with CrCLR, four of the six meniscal tears identified by arthrotomy were folded caudal horn. This lesion causes cranial displacement of the caudal horn which may have facilitated its identification by minimally invasive arthrotomy, being the probable reason for its high incidence in this study. Echogenicity and echotexture changes without affecting the meniscus morphology were related with intrasubstance degeneration described in human medicine. Ultrasonography is not the better technique to assess the CrCL but can assist in identifying partial ruptures. Because it has results similar to magnetic resonance imaging, ultrasonography is an important tool in the diagnosis of meniscus tears.